Orientation-dependent indentation reveals the crosslink-mediated deformation mechanisms of collagen fibrils. (1st March 2023) - Ostadi Moghaddam, A.; Arshee, M.R.; Lin, Z.; Sivaguru, M.; Phillips, H.; McFarlin, B.L.; Toussaint, K.C.; Wagoner Johnson, A.J.
Abstract: The spatial arrangement and interactions of the extracellular matrix (ECM) components control the mechanical behavior of tissue at multiple length scales. Changes in microscale deformation mechanisms affect tissue function and are often hallmarks of remodeling and disease. Despite their importance, the deformation mechanisms that modulate the mechanical behavior of collagenous tissue, particularly in indentation and compression modes of deformation, remain poorly understood. Here, we develop an integrated computational and experimental approach to investigate the deformation mechanisms of collagenous tissue at the microscale. While the complex deformation arising from indentation with a spherical probe is often considered a pitfall rather than an opportunity, we leverage this orientation-dependent deformation to examine the shear-regulated interactions of collagen fibrils and the role of crosslinks in modulating these interactions. We specifically examine tendon and cervix, two tissues rich in collagen with quite different microstructures and mechanical functions. We find that interacting, crosslinked collagen fibrils resist microscale longitudinal compressive forces, while widely used constitutive models fail to capture this behavior. The reorientation of collagen fibrils tunes the compressive stiffness of complex tissues like cervix. This study offers new insights into the mechanical behavior of collagen fibrils during indentation, and more generally, under longitudinal compressive forces, and illustrates the mechanisms that contribute to the experimentally observed orientation-dependent mechanical behavior. Statement of significance: Remodeling and disease can affect the deformation and interaction of tissue constituents, and thus mechanical function of tissue. Yet, the microscale deformation mechanisms are not well characterized in many tissues. Here, we develop a combined experimental-computational approach to infer the microscale deformation mechanisms of collagenous tissues with very different functions: tendon and cervix. Results show that collagen fibrils resist microscale forces along their length, though widely-used constitutive models do not account for this mechanism. This deformation process partially modulates the compressive stiffness of complex tissues such as cervix. Computational modeling shows that crosslink-mediated shear deformations are central to this unexpected behavior. This study offers new insights into the deformation mechanisms of collagenous tissue and the function of collagen crosslinkers. Graphical abstract: Image, graphical abstract